Obtenção de espumas de poliuretano a partir de coprodutos da cadeia dos biocombustíveis e resíduos agroindustriais - Camila Santana Carriço (2017)
The use of alternatives raw materials in polyurethane foams synthesis has been increasingly studied in recent years. In this sense, the use of residues from biofuels production and agroindustrial waste production is promising, considering that large volumes of biomass are generated in these chains, which are compatible with those demanded by polymers. In this work, lignin, crude glycerol, castor oil, cashew nut shell liquid, curauá fiber and macaúba pulp were the raw materials studied for the polyols preparation in order to synthesize polyurethane foams for different applications. These compounds were obtained from physical mixing and liquefaction methods. The polyols obtained were characterized by infrared spectroscopy, thermogravimetric analysis, hydroxyl number and viscosity. The polyols hydroxyl number presented values around 150 à 1050 mg KOH g-1. The effect of catalyst amount (2, 5 and 7% w/w), catalyst type (sulfuric acid and sodium hydroxide), reaction time (0.5, 1 and 1.5 h) and solvent / biomass molar ratio (2: 1, 3.5: 1 and 5: 1) were investigated on the macaúba pulp liquefaction. The effect of the NCO/OH molar ratio (1.1, 1.5 and 2.0), type (water, cyclopentane and n-pentane) and amount (2.4 and 6% w/w) of blowing agent, type (DBTDL and DABCO) and amount (1 and 2% w/w)of catalyst, addition of charge and addition of nanostructures (cellulose nanocrystals, clay and carbon nanotubes) were the parameters evaluated to produce the foams from the renewable polyols. The foams were characterized by infrared spectroscopy, thermogravimetric analysis, optical microscopy, scanning electron microscopy, apparent density, compressive strength, elastic modulus and thermal conductivity. The foams obtained presented similar properties to the petrochemical derived foam, with values of apparent density from 13 to 120 kg m-3 and compressive strength between 1,2 e 170 kPa, using a more environmentally friendly technology, adding value to the processes and products.